Child citizenship and educational participation in the Perú study of the school population of 5th and 6th grade of the primary education level in the departments of San Martin, Cajamarca and Ica - Loayza, Jerjes (2019)
It is proposed to explore the participatory nature of the school population of the 5th and 6th grade of primary education in the process of serving rations and products of the National School Food Program of Peru of the level of primary education in the departments of San Martín, Cajamarca and Ica. Through the application of discussion groups and semi-structured interviews, adverse situations of conflict between students are identified that will cause a process of symbolic and physical violence blurring possible democratic processes of citizen participation. Gender gaps are also recognized between girls and boys, which will reinforce the existence of participatory patriarchal female inhibition structures.